2015
DOI: 10.3748/wjg.v21.i13.3850
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy for gastric cancer: What have we learned since INT0116?

Abstract: Gastric cancer is one of the main cancer-related causes of death worldwide. The curative treatment of gastric cancer consists of tumor resection and lymphadenectomy. However, surgical treatment alone is associated with high recurrence rates. Adjuvant treatment strategies have been studied over the last decades, but there have been controversial results from the initial studies. The pivotal INT0116 study demonstrated that the use of adjuvant chemoradiotherapy with 5-fluorouracil increases relapse-free and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…5-FU adjuvant therapy of GC significantly improves OS. 71 In this study, we found that high expression of CCNB1 predicted poor OS in GC patients who receive 5-FU-based chemotherapy treatment. Therefore, CCNB1 might be a potential therapy target for GC patients who receive 5-FU-based chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 55%
“…5-FU adjuvant therapy of GC significantly improves OS. 71 In this study, we found that high expression of CCNB1 predicted poor OS in GC patients who receive 5-FU-based chemotherapy treatment. Therefore, CCNB1 might be a potential therapy target for GC patients who receive 5-FU-based chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 55%
“…For patients at high risk of postoperative recurrence, adjuvant chemotherapy is recognized as the standard of care in the Far East . In our patient cohort, S‐1 monotherapy comprised the majority (90%) of treatment regimens for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended the use of perioperative chemotherapy for managing resectable gastric cancer. In another study Jácome [17], sought to examine the significance of the use of 5-fluorouracil in reducing cases of relapses and overall improvement in the adjuvant chemotherapy process. The study acknowledges that the use of 5-fluorouracil in the chemotherapy process has been adopted in the vast western region.…”
Section: Authormentioning
confidence: 99%